2011
DOI: 10.1634/theoncologist.2011-0001
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of the Neutropenic Diet: Fact or Fiction?

Abstract: There really should not be a debate about the use of neutropenic diet for cancer patients. Its usefulness has never been scientifically proven. However, neutropenic diets remain in place in many institutions even though their usefulness is controversial. Neutropenic diets were once thought to be important in protecting patients from having to succumb to infection from neutropenia while undergoing chemotherapy. Although food may contain harmful organisms and research has shown that bacterial translocation is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 15 publications
0
30
0
3
Order By: Relevance
“…19 Thus, the available data do not support the use of a special low-bacteria diet in neutropenic patients. 20 Despite the lack of evidence, surveys showed that 43-78% of the hospitals use a special neutropenic diet. We recommend considering basic principles such as: (1) washing hands before preparing food, (2) storing raw meat, fish, chicken in a way that avoids contamination of other food, (3) washing in hot water dishes and cutlery that contact raw meat before placing them in contact with other food, (4) using fresh food without any mold, (5) consumption of pasteurized juices and dairy products, (6) avoiding uncooked meats, seafood, eggs and unwashed fruits and vegetables; 20,21 and (7) avoiding raw nuts and dried fruits due to the risk of fungal spores.…”
Section: Prevention Of Infections By General Medical Management Of Aamentioning
confidence: 99%
“…19 Thus, the available data do not support the use of a special low-bacteria diet in neutropenic patients. 20 Despite the lack of evidence, surveys showed that 43-78% of the hospitals use a special neutropenic diet. We recommend considering basic principles such as: (1) washing hands before preparing food, (2) storing raw meat, fish, chicken in a way that avoids contamination of other food, (3) washing in hot water dishes and cutlery that contact raw meat before placing them in contact with other food, (4) using fresh food without any mold, (5) consumption of pasteurized juices and dairy products, (6) avoiding uncooked meats, seafood, eggs and unwashed fruits and vegetables; 20,21 and (7) avoiding raw nuts and dried fruits due to the risk of fungal spores.…”
Section: Prevention Of Infections By General Medical Management Of Aamentioning
confidence: 99%
“…Bu hastalarda şu an için öneriler temel gıda tüketimi-ne uygun olacak şekilde 1) çiğ et, deniz ürünü ve çiğ yumurta tüketmemeleri, 2) pastörize edilmiş süt ve süt ürünleri kullanmaları, 3) meyve ve sebzelerin iyice yıkanarak yenmesini içermektedir (10) . Hastaların …”
Section: Nötropeni̇k Hastalarda Beslenme (Nötropeni̇k Di̇yet)unclassified
“…The diet restricted all fresh fruits and vegetables from patients with neutropenia, with the intent to support germ-free or germ-reduced environments. In some cases, diet principles and restrictions were softened to allow family members to peel foods, such as oranges or bananas, to give to the patient (Jubelirer, 2011).…”
mentioning
confidence: 99%
“…That environment was popularized with reference to the television character "The Bubble Boy" (Jubelirer, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation